Organizational Change Management Strategies in Addressing Employee Social Resistance During Green IT Transition - Rahayu Mardikaningsih; Dewie Tri Wijayati Wardoyo (Bulletin of Science, Technology and Society, 2026)
The implementation of environmentally friendly technology (Green IT) in corporate environments frequently encounters significant barriers in the form of employee social resistance and behavioral opposition. This study aims to analyze the factors triggering workers' social resistance and to formulate an effective organizational change management strategy to support the Green IT transition. Utilizing a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and internal documentation analysis. The findings reveal that social resistance stems from anxieties regarding increased workloads, disruptions to daily routines, and a lack of understanding of sustainability benefits. The application of a change management strategy focused on open dialogue, environmental-based digital literacy training, participatory leadership, and incentive schemes significantly reduced employee resistance. This study concludes that the harmonious integration of technology, management strategy, and social readiness is the primary key to achieving sustainable organizational transformation.